Levels of Nursing Students’ Exposure to Colleague Violence and Affecting Factors: A Multicenter Cross-Sectional Study - Güngör, Serap; Kose Tosunoz, Ipek (La Medicina del Lavoro, 2024)
Background: Colleague violence experiences of students negatively affect their vocational education in the short term and their desire to stay in the profession in the long term. This study aims to determine the levels of colleague violence experienced by nursing students and the affecting factors in Türkiye. Methods: This study was conducted with second-, third-, and fourth-year nursing students (N = 703) from three state universities in three different provinces in Turkey. The data were collected using the “Student Information Form” and “The Scale of Exposure to Colleague Violence” with an online questionnaire. Descriptive statistics, the Independent Samples t-test, and the ANOVA test were employed for data analysis. Results: students’ total mean score on the scale was 46.72 ± 21.30. The “exposure to verbal/psychological violence” and “effect of violence on physical and mental health” subscales were 21.62 ± 10.09 and 25.10 ± 12.02, respectively. The most common reaction to the violence they were exposed to was “remain silent” (34.7%). Conclusions: nursing students were exposed to moderate levels of verbal/psychological colleague violence, and students’ physical and mental health were moderately affected by this violence. Most students remained silent as a response to colleague violence. This study contributed to the emergence of factors that affect and are related to colleagues’ violence. The results highlighted the need for programs that educate people about colleague violence and what should be done.